Chemical characterisation, antibacterial activity, and (nano)silver transformation of commercial personal care products exposed to household greywater. Issue 10 (13th September 2019) - Khaksar, Maryam; Vasileiadis, Sotirios; Sekine, Ryo; Brunetti, Gianluca; Scheckel, Kirk G.; Vasilev, Krasimir; Lombi, Enzo; Donner, Erica
Abstract : The objective of this study was to test the original speciation of silver (Ag) in eight different commercially available personal care products and investigate the chemical transformation of Ag during exposure to two types of synthetic greywater. Abstract : The objective of this study was to test the original speciation of silver (Ag) in eight different commercially available personal care products and investigate the chemical transformation of Ag during exposure to two types of synthetic greywater. The antimicrobial activity of the products was examined to determine the relationship between Ag content and speciation with the antibacterial functionality of the products. The Ag content of each product was quantified and X-ray absorption near-edge structure (XANES) analysis was used to investigate the initial speciation in the products and the changes occurring upon mixture with greywater. The results showed that the total Ag concentration in the products ranged from 17 to 30 mg kg −1, and was usually below the value reported on the label. Analyses revealed the complexity of Ag speciation in these products and highlighted the importance of characterisation studies to help elucidate the potential risks of nano-Ag in the environment. The antibacterial results confirmed that the antibacterial efficacy of the products depends on the concentration, form and speciation of Ag in the products, but is also significantly affected by product formulation. For instance, many of the products contained additional bactericidal ingredients, making it difficult to determine how much of the bactericidal effect was due directly to the Ag content/species. This paper offers some suggestions for standard methodologies to facilitate cross-comparison of potential risks across different studies and nano-enabled products.